Immunoinformatic prediction about potential novel vaccine in surface antigen fragment protein of Toxoplasma gondii - Hasheminasab, Seyed Sajjad; Maghsood, Hossein; Khalili, Sara (International Journal of Health, 2016)
Toxoplasmosis is one of the most widespread infections in animals and humans. The Toxoplasma gondii major surface antigen, called SAG1 or p30, is a highly immunogenic protein which has generated great interest as a diagnostic reagent, as a potential subunit vaccine, and for its role in invasion. In this study, the epitopes of Toxoplasma gondii SAG1 were identified using bioinformatics. Through the analysis of the outÂ¬put of both NetCTL and CTLPred, and B-cell epitope prediction, the position of all the epitopes were found and combined in four sequences. The different tasks including, T-cell and B-cell prediction, Antigenicity determination of the conserved peptides, Homology modeling, Allergenicity and epitope conservancy analysis were done on the conserved peptides. We predict that our proposed epitopes would also trigger an immune response in vitro.Immunoinformatic prediction about potential novel vaccine in surface antigen fragment protein of Toxoplasma gondii